Absence of genetic introgression between Elymus ciliaris and E. pendulinus (Triticeae: Poaceae) as shown by endosperm protein SDS-electrophoresis in connection with hypotheses of E. amurensis origin - A. V. Agafonov; E. V. Kobozeva; S. I. Tatkov (Вавиловский журнал генетики и селекции)
The StY-genome group of Elymus species is of special interest, most of its species ranges extending to Russia from southern frontier territories, mainly from China. The ranges of Elymus pendulinus, E. ciliaris and E. amurensis within Russia overlap in the southern part of the Russian Far East only. Elymus ciliaris is considered by Russian taxonomists to be phylogenetically close to E. pendulinus, while hybridization of these species gave rise to the independent species E. amurensis. Moreover, in China, E. amurensis is recognized as a variety of E. ciliaris. Endosperm protein polymorphism was studied by SDS-electrophoresis for the purpose to reveal species specificity in E. pendulinus, E. ciliaris, and E. amurensis from a number of localities in the Primorskii Krai. Accessions of species from places of their joint occurrence were analyzed to detect identical polypeptide components which could have appeared due to genetic introgression. Nevertheless, both electrophoretic images visual analyses and construction the dendrograms of populations with various similarity coefficients revealed a high species specificity of E. ciliaris и E. pendulinus but no signs of introgression in spite of the fact that the two species often grow in common ecotopes and even form sterile hybrids. No indications of the origin of E. amurensis from the highly distinct species E. ciliaris and E. pendulinus were found either.The necessity of biosystematic and experimental methods for confirmation of the origin and taxonomic rank of new and many recognized species in the genus Elymus is shown.